Cultures et politiques dans les Alpes contemporaines - Bernard Debarbieux (Revue de Géographie Alpine)
More than ever before, the Alps are affected by increasingly varied and powerful flows and equally by the multiplication of initiatives designed to strengthen or regenerate the idea of “locality” (place). What spatialities and what territorialities activate the populations of the Alps today? What are the contemporary figures relating to circulation and flows and the complementary figures concerning spatial “anchoring” or fixity and new territorial foundations? These are the questions that this essay, proposes to develop. This text takes another look at the subject of a lecture given as part of celebrations to mark the centenary of the Institut de Géographie Alpine. This lecture, like the others given on this occasion, adopted a free format, presenting a report on the current situation in the Alps and prospects for the future. The written format adopted here logically takes the form of an essay. Readers looking for detailed illustrations and references are referred to three scientific articles published by the same author over recent years (see Appendix).